The Scroll and the Cross : 1,000 Years of Jewish-Hispanic Literature. - Stavans, Ilan (Taylor and Francis, 2013)
Jews and Latinos have been unlikely partners through tumultuous times. This groundbreaking, eclectic book of readings, edited by Ilan Stavans, whom The Washington Post described as ""one of our foremost cultural critics, "" offers a sideboard of the ups and downs of that partnership. It includes some seventy canonical authors, Jews and non-Jews alike, through whose diverse oeuvre-poetry, fiction, theater, personal and philosophical essays, correspondence, historical documents, and even kitchen recipes-the reader is able to navigate the shifting waters of history, from Spain in the tenth century.